2020
DOI: 10.1021/acs.jpcc.0c07024
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Study of Iron Oxide Nanoparticle Monolayer Formation at Liquid/Liquid Interfaces by Using In Situ Small-Angle X-ray Scattering

Abstract: Spatial and temporal small-angle X-ray scattering (SAXS) scans show that 8.6 and 11.8 nm iron oxide nanoparticles (NPs) in heptane drop-cast on top of a heptane layer atop a diethylene glycol (DEG) layer are trapped at the DEG/heptane interface to generally form a single ordered, hexagonal-close packed monolayer (ML), and this occurs long before the heptane evaporates. Many NPs remain dispersed in the heptane after this NP assembly. Assembly occurs faster than expected from considering only the diffusion of NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Overall, randomly dispersed AuNPs 15nm @PS 12k transforming into fcc multilayers and finally a 2D hexagonal packed superlattice during the NP construction process at the diethylene glycol interface can be observed. This result is in accordance to the observation of Herman et al, who studied the spreading process of iron oxide NP dispersion at the heptane/diethylene glycol interface. They found that the NPs formed a two-dimensional hexagonal close-packed monolayer before the solvent completely volatilized, and the NP spacing gradually decreased with solvent volatilization.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, randomly dispersed AuNPs 15nm @PS 12k transforming into fcc multilayers and finally a 2D hexagonal packed superlattice during the NP construction process at the diethylene glycol interface can be observed. This result is in accordance to the observation of Herman et al, who studied the spreading process of iron oxide NP dispersion at the heptane/diethylene glycol interface. They found that the NPs formed a two-dimensional hexagonal close-packed monolayer before the solvent completely volatilized, and the NP spacing gradually decreased with solvent volatilization.…”
Section: Resultsmentioning
confidence: 99%
“…The early stages of the self-assembly process of iron oxide nanoparticles in a fast-drying colloidal drop were studied with GISAXS with a temporal resolution down to milliseconds, leading to assemblies with a perfect hexagonal close-packed array within domains with less than 100 nm extension. 270 Hu et al 271 applied vertical scans with transmission SAXS near the liquid interface to identify the region of concentrated NPs and the degree of order above the interface. Mishra et al 272 reported the influence of wetting vs. dewetting properties of the solvent on the film morphologies of iron oxide nanoparticles on solid substrates.…”
Section: Reflectometry and Grazing-incidence Scatteringmentioning
confidence: 99%
“…The early stages of the self-assembly process of iron oxide nanoparticles in a fast-drying colloidal drop were studied with GISAXS with a temporal resolution down to milliseconds, leading to assemblies with a perfect hexagonal close-packed array within domains with less than 100 nm extension. 270 Hu et al 271 applied vertical scans with transmission SAXS near the liquid interface to identify the region of concentrated NPs and the degree of order above the interface. Mishra et al 272 reported the in-fluence of wetting vs. dewetting properties of the solvent on the film morphologies of iron oxide nanoparticles on solid substrates.…”
Section: Lateral and 3d Nanostructurementioning
confidence: 99%